2010
DOI: 10.1111/j.1939-0025.2010.01027.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Hurricane Katrina on the mental and physical health of low-income parents in New Orleans.

Abstract: The purpose of this study was to document changes in mental and physical health among 392 low-income parents exposed to Hurricane Katrina and to explore how hurricane-related stressors and loss relate to post-Katrina well being. The prevalence of probable serious mental illness doubled, and nearly half of the respondents exhibited probable PTSD. Higher levels of hurricane-related loss and stressors were generally associated with worse health outcomes, controlling for baseline socio-demographic and health measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
139
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(155 citation statements)
references
References 66 publications
9
139
0
1
Order By: Relevance
“…Although studies suggest that psychiatric comorbidity and prior traumas or disaster exposures may predispose patients to worse outcomes post-event, 11,14,21 there is also evidence that psychiatric comorbidity may be associated with greater treatment adherence among buprenorphine patients, potentially offsetting such liabilities. [22][23][24] In part, better outcomes may be related to buprenorphine activity at the kappa receptor counteracting stress-related and dysphoric symptoms.…”
Section: Post-disaster Outcomes Among Patients Enrolled In Addiction mentioning
confidence: 99%
See 1 more Smart Citation
“…Although studies suggest that psychiatric comorbidity and prior traumas or disaster exposures may predispose patients to worse outcomes post-event, 11,14,21 there is also evidence that psychiatric comorbidity may be associated with greater treatment adherence among buprenorphine patients, potentially offsetting such liabilities. [22][23][24] In part, better outcomes may be related to buprenorphine activity at the kappa receptor counteracting stress-related and dysphoric symptoms.…”
Section: Post-disaster Outcomes Among Patients Enrolled In Addiction mentioning
confidence: 99%
“…12 By contrast, Rhodes et al found in a subsequent study of Hurricane Katrina survivors that although severity of exposure affects symptomatology, demographic and other external factors may have more robust predictive power of patient outcomes in response to exposure than originally thought. 14 A smaller body of literature focuses on: (1) mental health issues related to addiction treatment peri-disaster (e.g., outcomes among patients in addiction treatment peri-event, including patients on methadone maintenance or who have recently completed inpatient programs), or (2) mental health services utilization (e.g., rates of patients seeking psychotherapy post 9/11). Regarding substance use, relapse rates post-event, and psychiatric comorbidity, studies document a variety of findings.…”
Section: Introductionmentioning
confidence: 99%
“…A high incidence (30.6%) of post-traumatic stress disorder was reported after a cyclone that struck India in 1999, 39 and a high prevalence of post-traumatic stress disorder and major depressive symptoms have also been reported following cyclones in India, Nicaragua, Sri Lanka and the USA. [40][41][42][43][44] These mentalhealth problems might have long-term impacts on health. However, these issues have so far been neglected in Bangladesh because of limited resources and poor health infrastructure.…”
Section: Policy and Practicementioning
confidence: 99%
“…7 In a similar fashion to Hurricane Matthew, which appears to have impacted impoverished, cholera-stricken regions of Haiti more heavily than developed regions in the United States, 1-3 Hurricane Katrina is known for its disproportionate impact on African-American citizens of New Orleans. Socioeconomic factors such as poor living conditions, 6 lack of transportation, 8 and a lower pre-hurricane income, 8 left impoverished members of the African-American population vulnerable and more likely to suffer from mental illness compared to higher income counterparts. 6,8 Additionally, among children and adolescents exposed to hurricane-related stressors, those living in poverty were found at greater risk of developing sustained emotional disturbances, including post-traumatic stress disorder (PTSD), behavioural disorders, and other diagnosable forms of mental illness.…”
Section: Selection Of Historical Precedentmentioning
confidence: 99%